Growth Performance of Sea Grapes (Caulerpa racemosa) in Sil-vofishery Ponds with Different Depths in Demak Village, Central Ja-va: Growth Performance of Sea Grapes (Caulerpa racemosa) in Silvofishery Ponds of Different Depths in Demak Village, Central Java - Nurasih, Nok Ayu; Rejeki, Sri; Dewi, Eko Nurcahya (Department of Aquaculture, 2026)
Caulerpa racemosa, often known as sea grapes, is an economically important macroalgae species from the Chlorophyceae group. Its growth is highly dependent on the nutrients in the waters; it needs to be cultivated with an integrated system, such as silviofishery. Silvofishery is an integrated system between mangroves and brackish water aquaculture. This study aims to analyze the effect of differences in cultivation depth on the growth performance of C. racemosa in silvofishery ponds. The treatments of this study were C. racemosa cultivated in silvofishery ponds at a depth of 20 cm and 60 cm. The measured parameters were total weight, SGR (Specific Growth rate), and water quality. The results of total weight indicated that C. racemosa cultivated at a depth of 20 cm showed a higher value (315.33±63.13 grams) compared to 60 cm (193.33±22.74 grams). The results of SGR measurements showed that C. racemosa cultivated at a depth of 20 cm (2.46±0.25 %/day) was higher than 60 cm (1.79±0.13 %/day). Temperature (27.5–33.7°C), pH (7.32–8.6), salinity (24–40 ppt), brightness (25–37.5 cm), and phosphate (0.2–1.6 mg/l) have not met the eligibility standards. Only nitrate (0.2–1.6 mg/l) and ammonia (0.1–0.4 mg/l) have reasonable water quality values. C. racemosa cultivated in Silvofishery Pound showed the best results at a depth of 20 cm, though the water quality was not optimum. We recommend further improvement to enhance the water quality so that its growth will be more optimal.